Hybrid fibre reinforcement of limestone calcined clay cement (LC3) mortar: An approach to optimised strength and fire resistance performance - Asmaa A. Selim; H. Shoukry; Mohamed S. Saif; Gamal E. Abdelaziz (Next Materials)
Green construction materials with enhanced fire resistance are a promising approach to improve fire safety and sustainability in the construction sector. Limestone Calcined Clay Cement (LC3) is a unique, innovative binder that incorporates calcined clay and limestone to replace clinker, reducing CO₂ emissions by up to 40 %. The LC3 has demonstrated mechanical and durability properties comparable to those of typical Portland Cement (OPC), thereby promoting sustainable infrastructure development. The fire resistance of LC3 composites is still a critical issue, especially when they are employed in constructions susceptible to high temperatures that could weaken them or cause them to explode. To address this issue, this study investigated the mechanical and fire-resistant performances of LC3-based mortars incorporating polypropylene (PP) fibre, basalt (BS) fibre, and their hybrid combinations (PP-BS). By replacing 60 wt% of OPC with a blend of metakaolin (MK) and limestone (LS) with MK:LS of 2:1, an eco-economic LC3 alternative binder has been prepared. PP and BS fibres have been added at various wt% percentages to LC3-based sand mortars. The compressive strength, flexural strength, and post-fire residual strength have been determined for LC3 mortars reinforced with PP, BS, and PP-BS fibres. After an hour of exposure to the ASTM E119 cellulosic fire curve, the LC3-plain mortar without fibre experienced complete failure, i.e., 0 % residual strength. However, the 0.3 % PP-reinforced LC3 mortar exhibited the best residual results, retaining 66.46 % and 18.78 % of its original compressive and flexural strength. Hybrid LC3 composites have also been prepared by adding BS fibres at different levels, ranging from 0.25 to 1.25 wt% to the 0.3 % PP-reinforced LC3 optimum mortar. While the BS-reinforced LC3 mortar experienced explosive failures under the rapid-fire exposure, the hybrid fibre-reinforced mortars demonstrated superior performance. The results suggest that hybrid fibre reinforcement offers a balanced solution, improving the overall mechanical properties and fire resistance compared to single-fibre and fibre-free systems.